Prevalence and correlation of workload and musculoskeletal disorders in industrial workers: a cross-sectional study - Rodríguez-Pulido, Anderson G.; Arrieta-Córdova, Andy F.; Arce-Huamani, Miguel A. (Frontiers in Rehabilitation Sciences, 2025)
BackgroundMusculoskeletal disorders (MSDs) are a leading cause of disability among industrial workers worldwide, often resulting from excessive physical and mental workload. This study aimed to determine the prevalence of MSDs and their correlation with workload including physical and mental dimensions among industrial workers in the cleaning and ballasting division of a Peruvian shipyard.MethodsA cross-sectional, correlational study was conducted in 2023 among 100 workers selected from a population of 134. Workload was assessed using a validated questionnaire covering physical and mental dimensions, while MSDs were evaluated with the standardized Nordic Musculoskeletal Questionnaire. Descriptive statistics summarized the prevalence of workload and MSDs, and the relationship between variables was analyzed using Spearman's correlation coefficient, considering a significance threshold of p < 0.05.ResultsHigh workload was identified in 85% of workers, with both physical and mental workload dimensions reaching high levels in the same proportion. The prevalence of severe MSDs was 88%, affecting primarily the wrist/hand, neck, shoulder, lumbar region, and elbow/forearm. A strong and statistically significant positive correlation was found between overall workload and MSDs (Spearman's rho = 0.896, p < 0.001). Similar correlations were observed for the physical (rho = 0.834) and mental (rho = 0.896) workload dimensions.ConclusionSevere musculoskeletal disorders are highly prevalent among industrial workers exposed to substantial physical and mental workload. The strong correlations observed highlight the need for comprehensive occupational health strategies that address both ergonomic and psychosocial risk factors to reduce the burden of MSDs in industrial settings.